Psychophysiological states and special performance of boxers with different styles of fight - Aksutin, V. V.; Korobeynikov, G. V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: The style of the fight is one of the important factors that affect the quality of the arts in boxing. Particularly important factor in the modern boxing are the mental processes that are involved in forecasting and analyzing the situation that arises in the ring and are associated with cognitive functions. Purpose - to examine the psychophysiological state and a special performance for skilled boxers with different styles of input match.